Laboratory manual of organic chemistry - Čižmáriková, Ružena, 1947-; Univerzita Komenského v Bratislave. Farmaceutická fakulta (Bratislava : Comenius University in Bratislava, 2012)
This manual includes general instruction for work in the chemical laboratory. For example: purification techniques, identification and characterization of organic compounds, molecular modeling, synthesis of organic compounds, equipment of laboratory desk, chemicals for practical exercises.
Keywords: chémia organická; zdravie pri práci; chemikálie organické; techniky investigatívne; modelovanie molekulovej štruktúry liekov; purifikácia; učebnica; príklady a cvičenia